Zinc and iron nutrition status in the Philippines population and local soils: a review - Palanog, Alvin D.; Calayugan, Mark Ian C.; Descalsota-Empleo, Gwen Iris; Amparado, Amery; Inabangan-Asilo, Mary Ann; Arocena, Emily C.; Sta. Cruz, Pompe C.; Borromeo, Teresita H.; Lalusin, Antonio; Hernandez, Jose E.; Acuin, Cecilia; Reinke, Russell; et al. (Frontiers Media, 2019)
The Philippines is one of the major rice-producing and rice-consuming countries of Asia. A large portion of its population depends on rice for their daily caloric intake and nutritional needs. The lack of dietary diversity among poor communities has led to nutritional consequences, particularly micronutrient deficiencies. Iron-deficiency anemia (IDA) and zinc deficiency (ZnD) are two serious nutritional problems that affect the health and economic sector of the country. Since rice dominates the Filipino diet by default, biofortification of rice will help improve the micronutrient status. The Philippine government has proactively initiated various programs and policies to address micronutrient deficiencies, particularly through fortification of basic food commodities. Biofortification, the fortification of rice with micronutrients through breeding, is considered the most sustainable and cost-effective strategy that can benefit large vulnerable populations. However, developing promising genotypes with micronutrient-enriched grains should be coupled with improving micronutrient bioavailability in the soil in order to optimize biofortification. This review documents the prevailing soil Zn-deficiency problems in the major rice production areas in the Philippines that may influence the Zn nutritional status of the population. The article also reports on the biofortification efforts that have resulted in the development of two biofortified varieties approved for commercial release in the Philippines. As nutritional security is increasingly recognized as a priority area, greater efforts are required to develop biofortified rice varieties that suit both farmers’ and consumers’ preferences, and that can address these critical needs for human health in a sustainable and cost-effective manner